Amine-modified silica zeolite from coal gangue for CO2 capture. (15th August 2022) - Quan, Cui; Chu, Hua; Zhou, Yingying; Su, Sheng; Su, Ruirui; Gao, Ningbo
Highlights: Modification and application of silica zeolite derived from coal gangue were studied. The pore structure of silica zeolite was affected by pH and calcination temperatures. CO2 capture on modified silica zeolite increased with the increase of PEI loading. Abstract: During coal mining process, a large amount of coal gangue is produced. Due to its low utilization, accumulation of coal gangue has caused serious environmental pollutions. In this work, silica zeolite MCM-41 and amine-modified MCM-41 were prepared from coal gangue for CO2 capture. MCM-41 were prepared at different pH (8, 9, 10) and different calcination temperatures (450 °C, 500 °C, 550 °C) and the effects of pH and temperature were investigated. Polyethyleneimine (PEI), was loaded onto MCM-41 at different loadings (30%, 40%, 50%, 60%) to improve its CO2 capture performance. The CO2 capture capacity and cyclic stability of amine modified MCM-41 were also evaluated. The results showed that preparation pH and calcination temperature both have effect on MCM-41. The specific surface area reaches a maximum of 642.17 m 2 g −1 at 550 °C and pH of 9. Amine modification improves the CO2 capture ability of MCM-41. As the PEI loading amount increased from 0 to 60%, the CO2 capture capacity showed a significant improvement from 0.125 to 1.742 mmol g −1 . After 5 cycles, its CO2 uptake capacity still remained 70%.